STUDI KOMPARATIF KEPUASAN KERJA PERAWAT PNS DAN NON PNS DI RSUD RADEN MATTAHER JAMBI - Rino M (Jurnal Akademika Baiturrahim Jambi, 2017)
Background: Job satisfaction is a pleasant emotional disposition and loves his job. Someone who has a level of job satisfaction will have a positive feeling about the job, but the results are still a lot of nurses in hospitals nationally and internationally to feel dissatisfaction. Methods: This study aims to look at the comparative study of job satisfaction of nurses civil servants and non-civil servants in hospitals Raden Mattaher Jambi 2016. corss sectional study design using comparative. Samples were taken by proportional random sampling with 220 nurses civil servants and non-civil servants. Results: The test results obtained frequency distribution of job satisfaction variables that have a comparison between civil servants and non-civil nurses in hospitals Raden Mattaher Jambi is a nurse job satisfaction civil servants (43.6%) were dissatisfied and nurses non-civil servants (56.4%) were not satisfied. Based on the research showed that job satisfaction of nurses nurses civil servants and non-civil servants at the Hospital Raden matther Jambi not meet applicable standards.